Pengaruh Pengelolaan Dana Desa Terhadap Kesejahteraan Masyarakat Desa Di Kabupaten Bantul - Sukmarani, Wendri; Pur Dwiastuti , Maria Magdalena; Kholisoh , Luluk (Kajian Ekonomi dan Bisnis, 2025)
The Village Fund is allocated by the central government to every village in Indonesia with the aim of equitable development, improving village infrastructure and improving the welfare of village communities. Village funds are public funds that are used for the benefit of the general public. The management and use of village funds must be carried out based on the principles of accountability, transparency, and involve the community from budget preparation to reports that must be accountable to the public or the general public. The management of the Village Fund that is accountable, transparent, and has community involvement is an obligation for the village government, so that it is hoped that the objectives of the Village Fund will be achieved, namely to realize the welfare of the village community. Community involvement in the management of the Village Fund can also support the success of development. This study aims to examine the effect of Village Fund management on the welfare of village communities in Bantul Regency. The study used primary data collected from community respondents in village areas in Bantul Regency. The results of this study are accountability and community participation in using village funds affect the welfare of village communities. However, transparency in the use of village funds has no effect on the welfare of village communities.